2010
DOI: 10.1097/ncn.0b013e3181ec28d4
|View full text |Cite
|
Sign up to set email alerts
|

Pretest Online Discussion Groups to Augment Teaching and Learning

Abstract: Tests and final examination scores of three semesters of control students in a nursing foundation course were compared with tests and final examination scores of three semesters of participating students. Participating students were offered access to an asynchronous pretest online discussion activity with a faculty e-moderator. While the simplified Bloom's revised taxonomy assisted in creating appropriate preparatory test and final examination questions for pretest online discussion, Salmon's five-stage online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For example, in a study where students in an anatomy class had 8% of their grade linked to their participation in a discussion forum, 83% of the students found the boards useful in improving their team building and critical analysis skills [18]. This finding was replicated by Kuhn et al [19] who found that a moderated pretest discussion forum as a tool for facilitating communication between nursing students significantly improved students' grades. Valaitis et al [20] designed a discussion forum to facilitate the establishment of a virtual community of practice for Community Health Nurses.…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a study where students in an anatomy class had 8% of their grade linked to their participation in a discussion forum, 83% of the students found the boards useful in improving their team building and critical analysis skills [18]. This finding was replicated by Kuhn et al [19] who found that a moderated pretest discussion forum as a tool for facilitating communication between nursing students significantly improved students' grades. Valaitis et al [20] designed a discussion forum to facilitate the establishment of a virtual community of practice for Community Health Nurses.…”
Section: Introductionmentioning
confidence: 97%